The Influence of Brand Image and Atmosphere Store on Purchase Decision for Samsung Brand Smartphone with Buying Intervention as Intervening Variables - Dede Solihin; Ahyani Ahyani; Rahmad Setiawan (International Journal of Social Science and Business, 2021)
This study aims to analyze a brand image and store atmosphere on purchasing decisions with purchase intention as an intervening variable at the Samsung Experience Store Karawaci customers. This type of research is a quantitative descriptive study. This research is survey research. The number of samples in this study was 98 people who were determined using the accidental sampling technique. The data in this study were collected using an instrument in the form of a questionnaire. Data were analyzed using path analysis. The results showed that brand image has a significant effect on purchase intention with a path coefficient of (0.152), store atmosphere has a significant effect on purchase intention with a path coefficient of (0.769), purchase intention has a significant effect on purchasing decisions with a path coefficient of (0.305). ), brand image has a significant influence on purchasing decisions with a path coefficient of (0.140), store atmosphere has a significant influence on purchasing decisions with a path coefficient of (0.494), Purchase Interest cannot mediate the influence of the Brand Image variable on Purchasing Decisions This can be seen from a one-tailed probability 0.08417935> 0.05, the Purchase Interest variable can mediate the influence of the Store Atmosphere variable on Purchasing Decisions This can be seen from the one-tailed probability 0.00004590 <0.05. The implication of this research is for Samsung to further enhance its brand image by releasing new high-tech products and providing convenience for shopping for customers by increasing the store atmosphere for outlets that sell Samsung products.